The influence of the YouTube social network on the formation of public opinion - Anvarova Muqaddas Khamidjon qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: Youtube platform also has a lot of users. This platform, which is the second largest in the world after Facebook, was founded 19 years ago. Today, as of February 2024, the number of its customers has reached 2.7 billion users. It can be seen that 52% of Internet users use this platform at least once a month.